Tinjaun Yuridis Terhadap Media Sosial Yang Menyalahgunakan Dan Mengakibatkan Penyemaran Nama Baik (putusan : No574 K/pid.sus/MA/2018) - Sitompul, Pardamean; Manurung, Okmin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The misuse of social media that causes defamation Decision: No 574 K / pid.sus / MA / 2018, is one of the many legal problems that have been ensnared due to the misuse of social media. The author uses three types of data sources, namely primary data sources of data obtained from laws and Supreme Court decisions. And secondary data data obtained from law books, law magazines and legal writings. And the last is tertiary legal material is complementary legal material obtained from dictionaries and the internet. and data analysis using qualitative data which is data in the form of words that talk about statutory regulations. The results of the research show that in the application of law enforcement of the ITE Law article 27 paragraph 1 in conjunction with article 45 paragraph 1 there is still a sense of injustice for the community, factors that must also be considered in imposing sanctions on victims of Baiq Nuril. and sociology of law and a strong conscience against actions or decisions in law enforcement. In this case, the government should have strict supervision of the use of information technology. This is aimed at preventing and overcoming efficiently and effectively the act of defamation through social media.